The Relevance To Lesson Of English Literature In A Globalized World - Butar-Butar, Chintya Winda Natalia (Sean Institute, 2025)
In accordance with the results of the study, it can be explained that the things learned by students in Indonesia in studying English Literature in the current era of globalization are related to the cultural and historical contexts that are described through the process of integration between English literary works and the global context through critical understanding analysis through digital applications and analyzing both types of English literary works through real differences in terms of theme, story setting, message and relevance to current conditions. The research method used is a qualitative descriptive method, where the object of this research is students and school students in Indonesia who take English Literature courses using data collection techniques through literature studies. The results of the study describe that learning English literature in the current global era must be integrated with current conditions and critical understanding must be carried out by analyzing themes, story settings, messages and relevance to the current context.